Employee engagement as a mediator on HRM practices and employee performance relationship of ready-made garment industry in Bangladesh - Ahmed, Shaheen (2017)
The ready-made garment industry has made noteworthy contribution to the economy of Bangladesh that convinces the government to flourish its economy through industrialization than agriculture-based initiatives. With regards to this matter, practitioners and academicians are struggling to find the reasons for employees’ high performance. Thus, the objective of this study was to assess the relationship between human resource management practices and employee performance through employee engagement of the ready-made garment industry in Bangladesh since the majority of the manufacturing employees are involved in this industry. The study followed the survey method for the collection of data from 392 operational level employees of different garment factories situated at Ashulia in Bangladesh. The data of this study was analyzed using the Partial Least Squares (Structural Equation Modeling) technique. The relationship between the exogenous and the endogenous latent construct was measured through the calculation of beta value, t-value, and p-value. The study revealed that the relationship between human resource management practices and employee performance is statistically significant. Similarly, the relationship between human resource management practices and employee engagement is also significant statistically except the compensation and engagement relationship. Moreover, employee engagement and employee performance relationship is statistically significant. In contrast, employee engagement does not mediate the relationship between compensation and performance, while the other aspects of human resource management practices and employee performance relationships are partially mediated by employee engagement. The findings of this study are expected to assist policy- makers and practitioners in formulating effective measures for the enhancement of employee performance in developing countries like Bangladesh.